The Perception of Cursive Writing towards Spelling Accuracy among Year 3 Primary School Students - Smita Kaur Baljandar Singh; Wan Muhammad Hazym Hyqal bin Wan Hashim; Karthiggeyen Kumaresan (Journal of Translation, Linguistics and Literature, 2024)
Cursive writing has always been a part of our life to write. Its inclusion into the KSSR curriculum of Malaysian English classroom has brought about various positive remarks towards learning competency. However, there is an unexplored issue that worth noting focusing on cursive writing application towards improving spelling accuracy. There is limited research on this issue, thus it is worth to be researched. Hence this study aims to analyze the association between gender with application and motivation to use cursive writing for spelling accuracy. It also investigates the significant differences between males and females when focusing on application and motivation to use cursive writing for spelling accuracy. The instrument used is a questionnaire with 9 items. The items are divided into two dimensions, namely application and motivation. A total of 80 students participate din this study. SPSS Software was used to analyse the data given. The results show that there is no statistically significant association between gender , the application and motivation of using cursive writing. The study also found out that the female participants generally have higher application scores compared to male participants. Female participants also tend to have higher motivation scores compared to those male participants. There has been a positive feedback between the idea of cursive writing application towards improving spelling performance. The insertion of cursive writing in the national syllabus is indeed helpful for students to apply it in the classroom for the context of this study